New ventures on an ancient campus - Guy, Ian
This article surveys the past, present and future of Oxford Science Park and describes how it maintains a link between academic expertise and industrial success.
Continuing his reviews of links between academe and industry, Ian Guy describes the development and prospects of the Oxford Science Park.